Leaf and inflorescence axis anatomy of Brazilian species of Rapateoideae (Rapateaceae, Poales) - Daltin, Angela de Lima [UNESP]; Oriani, Aline [UNESP]; Scatena, Vera Lucia [UNESP] (Acad Brasileira De Ciencias, 2015)
The anatomy of leaves and inflorescence axes of Spathanthus (2 spp.), Rapatea (2 spp.), Cephalostemon (1 sp.), and Duckea (1 sp.) (Rapateoideae, Rapateaceae) was studied to identify useful characters for taxonomy. The cross-section shape of inflorescence axis differentiates the genera, while the cross-section shape and structure of leaf midrib has a specific value. The following characteristics are exclusive of Spathanthus: silica cells randomly distributed in the leaf epidermis; plicate chlorenchyma in the leaf blade; presence of fiber bundles in the mesophyll and in the inflorescence axis parenchyma. Spathanthus is also distinguished by the number, type and distribution of vascular bundles in the inflorescence axis. The genus Rapatea is characterized by the presence of stomata and silica cells only on the abaxial epidermis of the leaves and chlorenchyma composed of arm cells in the leaf blade. Characteristics with diagnostic value for Cephalostemon riedelianus are: leaf epidermal cells with straight to slightly sinuous walls in frontal view, inflorescence axes presenting a defined cortex, fiber bundles facing the larger vascular bundles and a fistulous pith. The anatomical characteristics of the leaves and inflorescence axes thus proved to be of taxonomic value in generic and specific levels. They are also useful to differentiate Rapateoideae from other subfamilies of Rapateaceae.
Keywords: Anatomy; Cephalostemon; Duckea; Poales; Rapatea; Rapateaceae; Spathanthus